2020
DOI: 10.1021/acsabm.0c00529
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Nanoparticles Derived from RAFT Polymerization for Effective Drug Delivery to Macrophages

Abstract: The functional-group tolerance and simplicity of reversible addition fragmentation chain transfer (RAFT) polymerization enables its use in the preparation of a wide range of functional polymer architectures for a variety of applications, including drug delivery. Given the role of tumor-associated macrophages (TAMs) in cancer and their dependence on the tyrosine kinase receptor FMS (CSF-1R), the key aim of this work was to achieve effective delivery of an FMS inhibitor to cells using a polymer delivery system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…These targeted NPs are biocompatible in vitro and in vivo at physiologically relevant doses, and thus, this study is the first to demonstrate mannose-conducted preferential mRNA delivery to TAMs in an in vivo model. Recently, Rushworth et al prepared a series of fluorescently labeled RAFT polymers based on a mannose monomer scaffold that can be assembled into mannosylated NPs and successfully internalized into macrophages via a macrophage MR [156].…”
Section: Mannosylated Nanoparticles (Nps)mentioning
confidence: 99%
“…These targeted NPs are biocompatible in vitro and in vivo at physiologically relevant doses, and thus, this study is the first to demonstrate mannose-conducted preferential mRNA delivery to TAMs in an in vivo model. Recently, Rushworth et al prepared a series of fluorescently labeled RAFT polymers based on a mannose monomer scaffold that can be assembled into mannosylated NPs and successfully internalized into macrophages via a macrophage MR [156].…”
Section: Mannosylated Nanoparticles (Nps)mentioning
confidence: 99%
“…We observed that the size of mucosomes increases after 32 h of incubation with serum (133 ± 57 nm vs 308 ± 97 nm, Figure S2, Supporting Information), a result that can be attributed to the large serum proteins. [75] The formation of the biomolecular corona is not necessarily associated with the hindering of the interaction of glycosylated nanoparticles with glycan-binding biomolecules. [76] To perform biodistribution studies, mucosomes were loaded with a fluorescent dye suitable for in vivo imaging tests.…”
Section: Enzymatic Stability Interaction With Serum and In Vivo Biodi...mentioning
confidence: 99%